PENGARUH LEVERAGE, UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP KUALITAS LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Gina Septiana; Dela Desta (Jurnal Bina Bangsa Ekonomika, 2021)
Profit quality is a profit that reflects the continuation of future earnings, which are determined by accrual components and cash conditions that indicate the company's actual financial performance. The manufacturing industry is one of the important sectors in the Indonesian economy. The purpose of this research is to determine the influence of leverage, the size of the company, and profitability on profit quality. The population of this study is all manufacturing companies listed on the Indonesia Stock Exchange which amounted to 169 companies. Sampling in this study using purposive sampling techniques so that as many as 56 companies were sampled. Data testing and analysis in this study uses regression data panel with the Eviews 8 program. The results of the analysis can be concluded that: Leverage has a positive effect on profit quality, The size of the company has no effect on the quality of profit and profitability negatively affects the quality of profit